Socio-economic factors correlating with illegal use of giraffe body parts - Arthur B. Muneza; Bernard Amakobe; Simon Kasaine; Daniel B. Kramer; Mwangi Githiru; Gary J. Roloff; Matt W. Hayward; Robert A. Montgomery (Oryx, 2023)
Unsustainable hunting, both illegal and legal, has led to the extirpation of many species. In the last 35 years giraffe Giraffa spp. populations have declined precipitously, with extinctions documented in seven African countries. Amongst the various reasons for these population declines, poaching is believed to play an important role in some areas. Giraffes are primarily hunted for consumption and for the use of their body parts as trophies and in traditional medicine. However, the socio-economic factors that correlate with the use of giraffe body parts are not well understood. We conducted our study in Tsavo Conservation Area, Kenya, which experiences high levels of poaching. We used semi-structured surveys amongst 331 households to document how giraffe body parts are typically acquired and their intended use (i.e. trophy, medicinal or consumptive). We then used logistic regression models to assess the correlations between nine socio-economic factors and the use of giraffe body parts. We found that giraffe body parts had mostly consumptive and trophy uses. One-time suppliers, opportunistic access and widely known markets were the most common means of acquiring giraffe body parts. Results from our models showed that three variables (gender: men, occupation: tourism worker, and land ownership) were correlated significantly and positively with the use of giraffe body parts. We describe the complex links between socio-economic factors and the use of giraffe body parts and highlight the importance of implementing mitigation measures adapted to local contexts to combat a challenge that many species of conservation concern are facing.